Evaluation of triazole and strobilurin group fungicides and their combinations against rice leaf blast under nursery conditions - Bhaskar, B; Jayalakshmi Devi, R Sarada; Kumar, S Vijay; Rajan, C P D; Prasad, M Srinivas (Indian Journal of Plant Protection, 2026)
Rice blast, caused by Magnaporthe oryzae, is a major constraint to rice production. A field experiment was conducted under nursery conditions to evaluate the efficacy of triazole, strobilurin, and their combination fungicides along with a biocontrol agent (Pseudomonas fluorescens) for the management of rice leaf blast. Significant differences were observed among treatments in reducing disease severity. The lowest Per cent Disease Index (PDI) was recorded with Trifloxystrobin + Tebuconazole @ 0.08% (13.33%), which resulted in the highest disease reduction (77.20%) over control. This was followed by Tricyclazole @ 0.06% (14.41%) and Pyraclostrobin @ 0.04% (18.14%), which were statistically on par. Combination fungicides such as azoxystrobin + tebuconazole and Azoxystrobin + Difenconazole showed moderate efficacy. Individual triazoles, Tebuconazole and Difenconazole, were comparatively less effective. The biocontrol agent Pseudomonas fluorescens recorded moderate disease suppression (PDI 35.90%) and was superiorto control. The study highlights the effectiveness of combination fungicides, particularly Trifloxystrobin + Tebuconazole, in managing rice blast under nursery conditions.